FORMULASI SEDIAAN SABUN PADAT DARI MINYAK NILAM (Pogostemon cablin Benth) - Nirwati Rusli (As-Syifaa Jurnal Farmasi, 2018)
Solid soap is a soap made from fat saponification reaction of solid sodium hydroxide, which is used to cleanse the body. Patchouli essential oil content of patchouli alcohol discount antibacterial and anti-inflammatory. One dosage appropriate to formulate patchouli essential oils to antibacterial soap is in the form of a solid. This research aims to create a solid soap preparation patchouli essential oils as antibacterial soap. Research conducted an experiment with solid soap making preparations to test a physical evaluation of solid soap include organoleptic test is the color, shape and scent, pH test, test foam height and stability test (cycling test). The results showed that the preparations are made which have different colors and scents are the same, because the process used for solid soap that is by the saponification reaction for 2 hours with temperature 70-800C, with the variation of patchouli essential oil 1%, 2%, 3% (b / b) as an ingredient additives and make use of the type of NaOH. From the result of the concentration of essential oils nilam varied, which makes different colors with the same scent, obtained pH between 7.77 to 9.70 with a height of 9 cm foam inside.